Pengembangan Budaya Keagamaan Berbasis Kearifan Lokal dalam Meningkatkan Kinerja Guru di Sekolah Menengah Atas - Moh. Rofiki; Aminatus Zuhriyah; Eka Diana (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
This study aimed to determine the form of religious culture development based on local wisdom in Tunas Luhur Paiton High School and the factors that influence it. The type of research method used is descriptive qualitative. The subjects in this study were principals and high school teachers. This study found that developing a religious culture based on local wisdom has several forms: the habit of praying in the congregation, use of Islamic attributes, habituation of smiles, greetings, greetings (Senyum, Sapa, Salam-3S), availability of Islamic facilities, and celebration of Islamic holidays. The factors that support religious culture development are motivation and a pleasant work climate.